Clinical Manifestations and Outcomes of Ocular Graft Versus Host Disease following Allogeneic Stem Cell Transplantation - Vijay Shetty; Priyanka Kashelkar; Sachin Punatar; Suhas Haldipurkar; Abhishek Hoshing; Rasika Thakur; Prachi Sankhe; Shabnam Tanwar; Tanvi Haldipurkar; Maninder Singh Setia; Anant Gokarn; Lingaraj Nayak; et al. (Journal of Ophthalmic & Vision Research, 2024)
Abstract Purpose: To evaluate clinical presentation of chronic ocular graft-versus-host disease (GVHD), laterality of presentation, and longitudinal changes in patients undergoing allogeneic stem cell transplantation. Methods: This is a retrospective longitudinal analysis of 60 eyes from 30 patients who had undergone hematopoietic stem cell transplantation. Demographic characteristics, clinical history, comorbidities, and other organ involvements were taken into account for analysis. We also undertook complete evaluation of the eyes, including cornea and anterior segment, posterior segment, Schirmer test, tear break-up time, ocular surface disease index, and intraocular pressure. Results: The mean age of the patients was 34.3 ± 11 years. The mean time for the diagnosis of ocular GVHD was 232.8 days (95% CI: 153.6, 311.9). The common findings at the first visit were bilateral blepharitis (n = 5, 17%), meibomitis (n = 4, 13%), and conjunctival congestion (n = 3, 10%). While bilateral cataract was present in one (3%) patient at the first visit, at 18 months, five (17%) patients had bilateral cataract and one (3%) patient had unilateral cataract. Grade 1 (n = 17), grade 2 (n = 9), and grade 3 (n = 4) superficial punctate epithelial erosions (SPEEs) were also observed at the first visit. However, SPEEs were seen in only 11 eyes at 18 months; all of these cases were grade 1 SPEEs. Long-term findings included cataract, telangiectasia, blepharospasm, conjunctival congestion, grade 1 SPEEs, corneal filaments, and tear film debris. Conclusion: Although the initial presentations were SPEEs, meibomitis, blepharitis, and conjunctival congestion, these inflammatory conditions were reduced over time with proper management. However, there was an increase in the proportion of patients with cataract. It is important to regularly monitor these patients in order to identify and manage the initial as well as the late ocular manifestations of chronic GVHD.